Painting, Literature and Film in Colombian Feminine Culture, 1940-2005: Of Border Guards, Nomads and Women - Martin, Deborah (Cambridge University Press, 2013)
This book explores crucial moments in the emergence of feminine culture in Colombia hitherto unexamined in English-language criticism through an examination of the work of ground-breaking artist Débora Arango, best-selling novelist Laura Restrepo, and three generations of documentary filmmakers.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Proposition avant-garde: a view from the South - Kapur, Geeta (Art journal / College Art Association of America., 2018)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Toward a Postcolonial Sociology: The View from Latin America - Bortoluci, José H; Jansen, Robert S (2013)
While sharing fundamental similarities with other colonial and post-colonial experiences, Latin America has a unique history of having been the proving ground for early Spanish and Portuguese imperial projects, of having experienced a relatively long duration of – but also historically early end to – these projects, and of negotiating a particular and complex trajectory of internal and external post-colonial relations. What can the study of this distinct colonial and post-colonial experience contribute to a broader program of postcolonial sociology? Conversely, what can a revitalized postcolonial sociology contribute to the study of Latin America? This article develops provisional answers to these questions by reviewing major currents in South and North American scholarship on the Latin American colonial and post-colonial experience. Some of this scholarship self-consciously identifies with broader movements in postcolonial studies; but much of it – both historical and contemporary – does not. By bringing together diverse strands of thought, this article sheds new light on what postcolonialism means in the Latin American context, while using the comparative leverage that this set of often overlooked cases provides to contribute to a new program of postcolonial sociology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Épistémologies du Sud, pensées et féminismes décoloniaux latino-américains - Coenga-Oliveira, Danielle (Revue Possibles, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

La conscience de la Mestiza. Vers une nouvelle conscience - Anzaldúa, Gloria (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2011)
Gloria Anzaldúa a délibérément écrit certains mots et certaines phrases en espagnol-chicano tout au long de cet article, choisissant pour des raisons politiques et esthétiques de produire un texte qui s’adresse à tout le monde mais peut être compris à des niveaux différents. Elle travaille ainsi aussi bien avec l’intelligibilité qu’avec la non-intelligibilité, liées au vécu et au positionnement social de chacun-e, au-delà de la langue elle-même. Pour tenter de respecter ce travail sur l’intelligibilité, nous avons procédé de la manière suivante. Dans certains cas, Anzaldúa a écrit une expression en espagno-chicano puis l’a traduite en anglais, nous avons alors procédé de la même manière. Dans les autres cas, nous avons laissé tel quel dans le corps du texte, ce qu’Anzaldúa a écrit en espagnol-chicano. Cependant, pour placer cette langue sur le même plan d’intelligibilité que l’anglais, pour le lectorat francophone, nous en proposons une traduction, en note. Enfin, nous avons ajouté un certain nombre de notes de contextualisation. Ainsi, les notes en lettres correspondent aux notes originales d’Anzaldúa, tandis que les notes en chiffres correspondent à la traduction de l’espagnol-chicano vers le français et enfin, les notes en i, ii, iii etc, correspondent aux notes des traductrices. Par ailleurs, deux termes sont particulièrement délicats à traduire : « raza » et « mestiza ». Au Mexique, le mot « raza » est polysémique. Au sens strict, il signifie « race », cependant son emploi actuel et courant n’implique aucune connotation raciale, mais plutôt populaire et affective (ma bande, mon quartier, ma famille élargie, les gens avec qui je m’identifie…), ce qui conduirait à le traduire plutôt par « peuple ». Nous avons donc choisi des traductions contextualisées, utilisant « race » pour la pensée de Vasconcelos (prise dans les courants racialistes internationaux des années vingt), et « peuple » pour la pensée d’Anzaldúa elle-même (qui l’utilise dans un sens actuel et populaire). L’ensemble de son œuvre montre amplement le caractère non-essentialiste de sa pensée, ce qui nous conforte dans ce choix. Enfin, le concept de « mestiza » (ou « mestizo ») possède au Mexique des connotations complexes et contradictoires. Il désigne une personne dominant-e par rapport à l’Indien-ne, mais aussi une personne dominé-e par rapport aux gens d’origine espagnole-européenne. Simultanément, il constitue l’archétype (positif) de la nouvelle « race » forgée dans l’ancienne colonie européenne transfigurée par l’indépendance puis la révolution. Pour Anzaldúa, le mot possède toutes ces connotations, mais signifie également la pluralité à l’intérieur de chaque être humain. Nous avons donc choisi de ne pas traduire le concept de « mestiza », qu’elle-même a décidé d’utiliser en espagnol, son article visant précisément à expliquer le sens nouveau qu’elle donne à la « nouvelle métisse ».
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Decolonizing the Global Renaissance: A View from the Andes - Cohen-Aponte, Ananda (The Globalization of Renaissance Art: A Critical Review, 2017)
The development of Global Renaissance art history has had an undeniable impact on the field of colonial Latin American art. Some of the earliest manifestations of this disciplinary partnership can be found in exhibitions, monographs, articles, and edited volumes produced around the quincentennial of Christopher Columbus’s 1492 voyage. Exhibitions such as Circa 1492 at the National Gallery and a wave of scholarly publications addressed the cataclysmic impact of the European invasion and subsequent colonization of the Americas at an epistemological, linguistic, political, biological, and aesthetic level. The year 1992 precipitated an outpouring of critical reflection on the history of colonialism in the Western hemisphere and its enduring legacies both within Latin America and its diasporic communities.
LIVRE COMPLET : http://www.worldcat.org/oclc/1126363993
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Memories of Underdevelopment: Art and the Decolonial Turn in Latin America, 1960-1985 - González, Julieta; Lerner, Sharon; Giunta, Andrea; Kanjo, Kathryn (Museum of Contemporary Art San Diego, 2018)
OCLC: 1056112657
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Coloniality of Power, Eurocentrism, and Latin America - Quijano, Anibal (Nepantla: Views from South, 2000)
What is termed globalization is the culmination of a process that began with the constitution of America and colonial/modern Eurocentered capitalism as a new global power. One of the fundamental axes of this model of power is the social classification of the world’s population around the idea of race, a mental construction that expresses the basic experience of colonial domination and pervades the more important dimensions of global power, including its specific rationality: Eurocentrism. The racial axis has a colonial origin and character, but it has proven to be more durable and stable than the colonialism in whose matrix it was established. Therefore, the model of power that is globally hegemonic today presupposes an element of coloniality. In what follows, my primary aim is to open up some of the theoretically necessary questions about the implications of coloniality of power regarding the history of Latin America.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Related with the Podcast "Interview with author, Dr. Laura Pérez"
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Revista N'oj : Issue No.2 (2020) Event was sponsored by the Latinx Research Center at the University of California, Berkeley
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Género, representación y nuevas tecnologías: mujeres y video en México - Pech, Cynthia (Revista mexicana de ciencias políticas y sociales, 2006)
En este artículo, se aborda la temática del video como tecnología de género. El video es el medio de creación artística que algunas mujeres están utilizando para crear lo que se puede llamar imá genes en femenino. Se hace un acercamiento al discurso feminista y los presupuestos teóricos que se han tomado para el análisis del discurso videográfico de las mujeres. Se presenta un breve análisis de los trabajos de las videastas Pola Weiss y Pilar Rodríguez.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créatrice; _Nettoyé

Coloniality at Large: Latin America and the Postcolonial Debate - Moraña, Mabel; Dussel, Enrique; Jáuregui, Carlos A. (Duke University Press, 2008)
Postcolonial theory has developed mainly in the U.S. academy, and it has focused chiefly on nineteenth-century and twentieth-century colonization and decolonization processes in Asia, Africa, the Middle East, and the Caribbean. Colonialism in Latin America originated centuries earlier, in the transoceanic adventures from which European modernity itself was born. Coloniality at Large brings together classic and new reflections on the theoretical implications of colonialism in Latin America. By pointing out its particular characteristics, the contributors highlight some of the philosophical and ideological blind spots of contemporary postcolonial theory as they offer a thorough analysis of that theory’s applicability to Latin America’s past and present. Written by internationally renowned scholars based in Latin America, the United States, and Europe, the essays reflect multiple disciplinary and ideological perspectives. Some are translated into English for the first time. The collection includes theoretical reflections, literary criticism, and historical and ethnographic case studies focused on Ecuador, Guatemala, Mexico, Brazil, the Andes, and the Caribbean. Contributors examine the relation of Marxist thought, dependency theory, and liberation theology to Latin Americans’ experience of and resistance to coloniality, and they emphasize the critique of Occidentalism and modernity as central to any understanding of the colonial project. Analyzing the many ways that Latin Americans have resisted imperialism and sought emancipation and sovereignty over several centuries, they delve into topics including violence, identity, otherness, memory, heterogeneity, and language. Contributors also explore Latin American intellectuals’ ambivalence about, or objections to, the “post” in postcolonial; to many, globalization and neoliberalism are the contemporary guises of colonialism in Latin America. Contributors : Arturo Arias, Gordon Brotherston, Santiago Castro-Gómez, Sara Castro-Klaren, Amaryll Chanady, Fernando Coronil, Román de la Campa, Enrique Dussel, Ramón Grosfoguel, Russell G. Hamilton, Peter Hulme, Carlos A. Jáuregui, Michael Löwy, Nelson Maldonado-Torres, José Antonio Mazzotti, Eduardo Mendieta, Walter D. Mignolo, Mario Roberto Morales, Mabel Moraña, Mary Louise Pratt, Aníbal Quijano, José Rabasa, Elzbieta Sklodowska, Catherine E. Walsh
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); _Nettoyé

Latin American Decolonial Thought, or Making the Subaltern Speak - Asher, Kiran (Geography Compass, 2013)
The Modernity/Coloniality/Decoloniality (MCD) research program is a collective project associated with Latin America. In addition to a critique of Eurocentric “colonial modernity,” the project highlights non-Eurocentric forms of knowing and being in the world. It also aims to foster alternative or decolonial thinking emerging from the lived colonial experiences of those situated “outside” Europe. This last is what MCD proponents claim differentiates it from postcolonial critiques of modernity with their emphasis on deconstruction. This review provides a brief but critical overview of the MCD project's parameters and claims. It makes a cautionary call to those tempted by “alternatives to modernity,” who might want to uncritically adopt alternative decolonial thinking. It concludes with a call for a closer and critical engagement with Latin American decolonial ideas and those they contest.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Re-Mapping Latin American Studies: Postcolonialism, Subaltern Studies, Postoccidentalism and Globalization Theory - Mendieta, Eduardo (Dispositio, 2005)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Corporeal Identities, Maternal Artivism: A New Decolonial Approach to the Study of Latin American Women Artists - Demori, Lara (Arts, 2019)
Stemming from Grosfoguel’s decolonial discourse, and particularly his enquiry on how to steer away from the alternative between Eurocentric universalism and third world fundamentalism in the production of knowledge, this article aims to respond to this query in relation to the field of the art produced by Latin American women artists in the past four decades. It does so by investigating the decolonial approach advanced by third world feminism (particularly scholar Chandra Talpade Mohanty) and by rescuing it from—what I reckon to be—a methodological impasse. It proposes to resolve such an issue by reclaiming transnational feminism as a way out from what I see as a fundamentalist and essentialist tactic. Following from a theoretically and methodological introduction, this essay analyzes the practice of Cuban-born artist Marta María Pérez Bravo, specifically looking at the photographic series Para Concebir (1985–1986); it proposes a decolonial reading of her work, which merges third world feminism’s nation-based approach with a transnational outlook, hence giving justice to the migration of goods, ideas, and people that Ella Shohat sees as deeply characterizing the contemporary cultural background. Finally, this article claims that Pérez Bravo’s oeuvre offers the visual articulation of a decolonial strategy, concurrently combining global with local concerns.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Sensing Decolonial Aesthetics in Latin American Arts - Ramos, Juan G. (University Press of Florida, 2018)
Bringing Latin American popular art out of the margins and into the center of serious scholarship, this book rethinks the cultural canon and recovers previously undervalued cultural forms as art. Juan Ramos uses "decolonial aesthetics," a theory that frees the idea of art from Eurocentric forms of expression and philosophies of the beautiful, to examine the long decade of the 1960s in Latin America–a time of cultural production that has not been studied extensively from a decolonial perspective. Ramos looks at examples of "antipoetry," unconventional verse that challenges canonical poets and often addresses urgent social concerns. He analyzes the militant popular songs of nueva canción by musicians such as Mercedes Sosa and Violeta Parra. He discusses films that use visually shocking images and melodramatic effects to tell the stories of Latin American nations. He asserts that these different art forms should not be studied in isolation but rather brought together as a network of contributions to decolonial art. These art forms, he argues, appeal to an aesthetic that involves all the senses. Instead of being outdated byproducts of their historical moments, they continue to influence Latin American cultural production today.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé